1990
DOI: 10.1002/cm.970150302
|View full text |Cite
|
Sign up to set email alerts
|

Actin‐dependent carotenoid droplet dispersion in permeabilized cultured goldfish xanthophores

Abstract: Organelle translocations are essential cellular processes. Although much progress has been made with regards to microtubule-dependent organelle translocations, little is known about actin-dependent organelle translocation(s) except cytoplasmic streaming in Nitella. On the other hand, there is indirect evidence that actin-dependent organelle translocation may be involved in secretion. We now present evidence that the dispersion of the pigment organelles carotenoid droplets in goldfish xanthophores is apparently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
1
16
1
1
Order By: Relevance
“…In xanthophores, pigment dispersion apparently did not involve microtubules [Chen and Wang, 1993] while ATP, F-actin, and phosphorylation of a p57 protein of carotenoid droplets were proposed to be indispensable for this event [Lynch et al, 1986;Tchen et al, 1988;Yu et al, 1990]. Treatment with anti-actin antibody, phalloidin, or DNAase in digitonin-treated xanthophores completely inhibited pigment dispersion [Yu et al, 1990].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In xanthophores, pigment dispersion apparently did not involve microtubules [Chen and Wang, 1993] while ATP, F-actin, and phosphorylation of a p57 protein of carotenoid droplets were proposed to be indispensable for this event [Lynch et al, 1986;Tchen et al, 1988;Yu et al, 1990]. Treatment with anti-actin antibody, phalloidin, or DNAase in digitonin-treated xanthophores completely inhibited pigment dispersion [Yu et al, 1990].…”
Section: Discussionmentioning
confidence: 97%
“…Treatment with anti-actin antibody, phalloidin, or DNAase in digitonin-treated xanthophores completely inhibited pigment dispersion [Yu et al, 1990].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular players in dispersion and aggregation were eludicated in permeabilized cell and cell-free systems (Lynch et al, 1981(Lynch et al, , 1986aPalazzo et al, 1989b;Tchen et al, 1988;Wu et al, 1990;Yu et al, 1989Yu et al, , 1990Zeng et al, 1989) along with the immunologic characterization of intermediate filaments (Walker et al, 1989) and the CD phosphoprotein, p57 (Gu, 1991). In order to carefully study the cytoskeleton, xanthophores were extracted and fixed after inducing different states of pigment distribution.…”
Section: Subsequent Studies: Permeabilizedmentioning
confidence: 98%
“…Although actin has been proposed to aid in the dispersion of pigments in permeabilized xanthophores (YU et al, 1990), no morphological evidence for a direct linkage between pigment granules and actin filaments has been demonstrated. Since only a limited amount of actin filaments is known to be present in the subplasmalemmal region, how this limited presence of actin filaments could be responsible for pigment dispersion throughout the cytoplasm remains to be explored.…”
Section: Translocationmentioning
confidence: 99%
“…For example, in melanophores pigment dispersion and partial or complete aggregation-though in a reduced rate-could be induced in the absence of microtubules (SCHLIWA and EUTENEUER, 1978;BECKERLE and PORTER, 1983;STEARNS and WANG, 1987b). In xanthophores, YU et al (1990) found that pigment dispersion in permeabilized xanthophores in vitro was, instead, actin-dependent, while microtubules participated only in the formation of the central pigment mass (CPM) (TCHEN et al, 1986;WALKER et al, 1989). Moreover, phosphorylation and dephosphorylation of some 57 kd polypeptides, found to coincide respectively with pigment dispersion and aggregation, were proposed to contribute to pigment movements in both xanthophores and melanophores (LYNCH et al, 1986a, b;ROZDZIAL and HAIMO, 1986 (WALKER et al, 1989).…”
mentioning
confidence: 99%